Reasoning of group constructive solutions of a roadbed on automobile roads’ areas in the conditions of cryolithic zone - T. V. Bobrova; A. A. Dubenkov (Вестник СибАДИ, 2017)
The authors propose a method for solving the problem of belonging group constructive solutions of a roadbed to areas with repetitive, along a route, engineering and geological conditions in design of roads on permafrost grounds. There is developed an algorithm of selecting effective options based on combinatorial method on criterion of minimizing total discounted costs for construction, major repair, repair and maintenance of a road construction during life cycle. The result of problem solution is structuring of an object, which serves as the basis for the organizational and technological design.